Dynamics of Moral Repair: Forgiveness, Self-Forgiveness, and the Restoration of Value Consensus as Interdependent Processes. (April 2021) - Wenzel, Michael; Woodyatt, Lydia; Okimoto, Tyler G.; Worthington, Everett L.
Most psychological research has investigated victims' forgiveness and offenders' self-forgiveness separately, ignoring interactive and dynamic processes between them. We suggest that both parties are interdependent in their attempts to revalidate the values violated by the wrongdoing. In the present study, both partners of close relationships dyads (including 164 complete couples) were surveyed over three time-points following the report of a wrongdoing by one of the partners. Latent growth modeling showed that victims' forgiveness was associated with growth in their perception of a value consensus with the offender. Victims' value consensus perception was associated with growth in offenders' perception of value consensus and engagement in genuine self-forgiveness (working through). However, directly, forgiveness was associated with decline in offenders' genuine self-forgiveness, while offenders' self-punitiveness was associated with decline in victims' forgiveness. The findings highlight the regulatory function of victim forgiveness and the pivotal role of restoring value consensus in interactive moral repair.